Blood biomarkers associated with all-cause mortality risk: Accessibility and clinical utility for lifestyle medicine - Matthew Halma; Mariyam Aniwar; Edgar Selem; Jack Tuszynski; Joseph Varon; Paul Marik (Archives of Gerontology and Geriatrics Plus)
Mortality associated biomarkers are advantageous in that they are strongly associated with general health. Disease specific biomarkers, if optimized for, can often create suboptimal outcomes in another area, thereby compromising the health of the measured person. We use an existing database of mortality associated blood biomarkers to assess their applicability as part of a general anti-aging protocol, and the cost effectiveness of a strategy relying on biomarker testing combined with targeted interventions to improve one's aging outlook. Early intervention for suboptimal biomarkers may yield health benefits in later age, and biomarker tests provide a means of intervening in negative health habits and promoting healthy behavior.